Evidence-based recommendations for economic evaluations in spine surgery: study protocol for a Delphi consensus. Issue 12 (23rd December 2021) - Droeghaag, Ruud; Schuermans, Valérie N E; Hermans, Sem M M; Smeets, Anouk Y J M; Caelers, Inge J M H; Hiligsmann, Mickaël; van Hemert, Wouter L W; Evers, Silvia; van Santbrink, Henk
Abstract : Introduction: Considering the rising global healthcare expenses, economic evaluations are more important than ever. Even though the number of studies regarding costs and cost-effectiveness is increasing, the quality of these studies remains relatively low. This is mainly caused by abundant heterogeneity in methods used for determining, calculating and reporting cost data, despite current general guidelines for the conduct of economic evaluations. Disease-specific recommendations for the conduct of economic evaluations in the field of spine surgery, as complement to existing general guidelines, will ameliorate overall research quality, comparability and interpretability and thus, the overall quality. We aim to provide expert-based recommendations for the design, conduct, and reporting of economic evaluations in spine surgery. Methods and analysis: A modified Delphi study will be conducted to formulate expert-based recommendations. The following steps will be taken: (1) The conduct of a systematic review to identify relevant publications and identify relevant authors. Formation of an expert group and a Delphi-panel. (2) Drafting of statements based on articles included in the systematic literature review. Validation of drafted statements by the expert group. Step 2 can be repeated up to three times, statements can be discarded and adjusted in these rounds. Statements with more than 75% agreement will be accepted as consensus statements. (3) Validation of statements by the Delphi-panel. (4) Final recommendations. Ethics and dissemination: The underlying work is based on existing literature and published data and does not include participation of patients, and thus does not require ethical review approval. The final recommendations are intended for (clinical) researchers in the field of cost-effectiveness in spine surgery. The Delphi method ensures that the final output reflects the opinions of international participants and gives insight in the adherence level to the recommendations. The aim is to reach uniformity in design, conduct and reporting of these studies, as is currently lacking. This will provide a solid basis to determine cost-effectiveness of spine surgeries and consequently aid to limit the rising healthcare costs. The findings of this study and the final recommendations will be disseminated in conferences and seminars and will be published in an international peer-reviewed journal.